Possible Green Power Marketing Strategies to Promote Solar Power in Sri Lanka - Ambepitiya, Kalpana (Journal of Entrepreneurship, Business and Economics; Vol 6 No 1 (2018), 2018)
The need to invest in alternative energy solutions to supplement the increasing demand for power by the growing national economy of Sri Lanka has become a significant issue at present. One of the approaches adopted by the country to address this issue is to promote the use of solar power in the household sector in order to reduce its dependence on the national power grid and to increase the energy efficiency in their daily activities. As the participation of the private sector is involved in this undertaking, the problem of identifying the most appropriate marketing methods that can be used to promote solar power in the household sector arises. This research by focusing on the problem has contributed to the green power marketing literature by identifying and applying four selected marketing strategies that can be used to market solar power in Sri Lanka. A descriptive research methodology has been used in this study by conducting a survey that was administered to a selected sample from a population that included 110 households and 25 marketing experts. The Study that was carried out over a period of eight months used a questionnaire and the online interview as survey instruments. It proposes a green power marketing framework for a solar power industry in Sri Lanka. The findings of this study present a convincing case that Cause-related, Community-based and personal selling strategies may work to promote solar power in Sri Lanka. Traditional methods like promotional marketing have little influence on customers. Potential customers also suggested that the marketing approach needs to be more environment-friendly and community based. In future researches it is advisable to study in different contexts such as emerging, developing and developed economies and making comparisons.  Research paper Keywords: Cause-related marketing, Community-based marketing, Green Power Marketing, Personal selling marketing, Promotional marketing, Solar power  Reference to this paper should be made as follows: Ambepitiya, K. (2018). Possible Green Power Marketing Strategies to Promote Solar Power in Sri Lanka, Journal of Entrepreneurship, Business and Economics , 6 (1), 166–204.